Mean platelet counts are relatively decreased with malaria but relatively increased with endemic Burkitt Lymphoma in Uganda, Tanzania, and Kenya - Peprah, Sally; Ogwang, Martin D.; Kerchan, Patrick; Reynolds, Steven J.; Tenge, Constance N.; Were, Pamela A.; Kuremu, Robert T.; Wekesa, Walter N.; Masalu, Nestory; Kawira, Esther; Kinyera, Tobias; Otim, Isaac; et al. (British journal of haematology, 2020)
Platelet counts are decreased in Plasmodium falciparum malaria, which is aetiologically linked with endemic Burkitt lymphoma (eBL). However, the pattern of platelet counts in eBL cases is unknown. We studied platelet counts in 582 eBL cases and 2 248 controls enrolled in a case-control study in Uganda, Tanzania and Kenya (2010–2016). Mean platelet counts in controls or eBL cases with or without malaria-infection in controls versus eBLcases were compared using Student’s t-test. Odds ratios (ORs) and two-sided 95% confidence intervals (95% CIs) were estimated using multiple logistic regression, controlling for age, sex, haemoglobin and white blood cell counts. Platelets were decreased with malaria infection in the controls [263 vs. 339 9 109 platelets/l, P < 0 0001; adjusted OR (aOR) = 3 42, 95% CI: 2 79–4 18] and eBL cases (314 vs. 367 9 109 platelets/ l, P-value = 0 002; aOR = 2 36, 95% CI: 1 49–3 73). Unexpectedly, platelets were elevated in eBL cases versus controls in overall analyses (mean: 353 vs. 307 9 109 platelets/l, P < 0 0001; aOR = 1 41; 95% CI: 1 12–1 77), and when restricted to malaria-positive (mean 314 vs. 263 9 109 platelets/ l, P < 0 0001; OR = 2 26; 95% CI: 1 56–3 27) or malaria-negative (mean 367 vs. 339 9 109 platelets/l, P < 0 001; OR = 1 46; 95% CI: 1 17–1 83) subjects. Platelets were decreased with malaria infection in controls and eBL cases but elevated with eBL.
Keywords: Burkitt lymphoma; Epidemiology; Epstein–Barr virus; Non- Hodgkin lymphoma; Plasmodium falciparum malaria; Platelet counts